Hypothermic pulsatile preservation of kidneys from uncontrolled deceased donors after cardiac arrest – a retrospective study. (12th September 2017) - Matillon, Xavier; Danjou, Fabrice; Petruzzo, Palmina; Thaunat, Olivier; Rimmele, Thomas; Delsuc, Claire; Faure, Alexandre; Rabeyrin, Maud; Meas Yedid, Vannary; Hanf, William; Morelon, Emmanuel; Badet, Lionel; et al.
Summary: Kidneys from uncontrolled donors after cardiac arrest (uDCD) suffer from a period of warm ischemia between cardiac arrest and cold flushing. Aim of the study was to evaluate renal outcomes of uDCD kidneys selected on the basis of renal Resistance Index (RI) and its influence on graft function and survival. The study included 44 kidneys procured from 26 uDCD starting 1.1.2006 until 12.31.2013. The donors (Maastricht category II) underwent cardiopulmonary resuscitation by assisted ventilation and chest compression; the organs were preserved with in situ cold perfusion or a normothermic regional perfusion. All kidneys were perfused on hypothermic (1–4 °C) pulsatile perfusion machine (RM3; Waters Medical System) and discarded when RI ≥0.5 mmHg/ml/min after 6 h of perfusion. There was one (2.2%) primary non function, while 37 recipients (84.1%) experienced delayed graft function. Graft survival was 97.6% at 1 and 3 post‐transplantation years. Linear regression models showed that lower values of RI at the end of perfusion were associated with higher values of Modification of Diet in Renal Disease at 3 ( P = 0.049) and 6 months after transplantation ( P = 0.010) and with higher values of inulin clearance at 1 year ( P = 0.030). RI showed to be a useful tool to select uDCD kidneys allowing to achieve good clinical results.